Pemanfaatan Game Based Learning dan Gamifikasi Adaptif dalam Pembelajaran STEM: Penelitian - Alim Nur Khafidh; Fitria Widyawati; Najarudin; Selvi Yani; Yeni Nuraeni; Indrawati; Virga Inesrawanti; Hari Abdus Salam; Fitri Damayanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The 21st-century education paradigm demands that students master critical thinking, collaboration, communication, and creativity skills (4C), which align with the Science, Technology, Engineering, and Mathematics (STEM) approach. However, the implementation of STEM education in Indonesia still faces challenges such as low student motivation, engagement, and problem-solving abilities. This study aims to examine the potential of utilizing Game-Based Learning (GBL) with adaptive gamification as an innovative strategy to overcome these obstacles. A qualitative research method was employed through a literature study approach, drawing data from national and international journal articles, conference proceedings, and academic books published within the last 5–10 years. Data were collected through academic database searches (Scopus, Google Scholar, DOAJ, and Sinta) and analyzed using content analysis techniques involving reduction, categorization, and synthesis of findings. The results indicate that GBL can enhance students’ intrinsic motivation, engagement, and academic performance in STEM learning, particularly when designed with authentic, adaptive, and reflective elements. The identified advantages include increased motivation, personalized learning, and improved problem-solving skills, whereas the limitations involve infrastructural readiness, teacher competence, and potential design-related distractions.